2013
DOI: 10.3109/02699052.2012.750748
|View full text |Cite
|
Sign up to set email alerts
|

The role of commonality, distinctiveness and importance of semantic features in persons with aphasia

Abstract: These results suggest that distinctive feature knowledge contributes in a significant way to the integrity of semantic representations in people with aphasia which can influence their performance of language tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 26 publications
8
11
4
Order By: Relevance
“…Furthermore, Mason-Baughman and Wallace (2013b) found significant differences in high-importance distinctive (HID) feature knowledge versus low-importance distinctive (LID) feature knowledge demonstrating that level of importance may also affect distinctive feature knowledge. However, Mason-Baughman and Wallace (2013a) indicated that distinctive mid- and low-importance features are not differentially impaired in people with aphasia, replicating the findings of Germani and Pierce (1995) and Cox (2009). Taken together, the results suggest that LID feature knowledge is the most impaired in people with aphasia and that mid-importance distinctive (MID) feature knowledge may be indiscernible from LID feature knowledge.…”
Section: Feature Knowledge: Role Of Importance and Distinctivenesssupporting
confidence: 70%
See 4 more Smart Citations
“…Furthermore, Mason-Baughman and Wallace (2013b) found significant differences in high-importance distinctive (HID) feature knowledge versus low-importance distinctive (LID) feature knowledge demonstrating that level of importance may also affect distinctive feature knowledge. However, Mason-Baughman and Wallace (2013a) indicated that distinctive mid- and low-importance features are not differentially impaired in people with aphasia, replicating the findings of Germani and Pierce (1995) and Cox (2009). Taken together, the results suggest that LID feature knowledge is the most impaired in people with aphasia and that mid-importance distinctive (MID) feature knowledge may be indiscernible from LID feature knowledge.…”
Section: Feature Knowledge: Role Of Importance and Distinctivenesssupporting
confidence: 70%
“…Feature knowledge was tested by having participants match features to target nouns presented in arrays of three semantically unrelated nouns. In addition, people have aphasia appear to have a decreased appreciation of distinctive features (Mason-Baughman, 2010; Mason-Baughman & Wallace, 2013a, 2013b).…”
Section: Feature Considerationsmentioning
confidence: 99%
See 3 more Smart Citations